2015
DOI: 10.1097/bot.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Proximal Tibiofibular Dislocation

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Outcomes of this particular injury pattern are largely unknown. PTFJ dislocations in the setting of tibia fracture have high rates of neurovascular injury and increased risk for complications, but these are typically associated with high-energy trauma and likely represent a different injury than that in our report 10 .…”
mentioning
confidence: 60%
“…Outcomes of this particular injury pattern are largely unknown. PTFJ dislocations in the setting of tibia fracture have high rates of neurovascular injury and increased risk for complications, but these are typically associated with high-energy trauma and likely represent a different injury than that in our report 10 .…”
mentioning
confidence: 60%
“…A recent review 3 notes that PTFD occurs in 1–2% of tibial shaft/plateau fractures, and is a marker of severe lower limb trauma. 31 cases of isolated PTFD have been published since 1974, 4 , 5 which have occurred following a wide range of mechanisms, 6 , 7 ranging from football 8 to long jump, 9 falling from a height 10 to snowboarding.…”
Section: Discussionmentioning
confidence: 99%
“…13 Superior and inferior dislocations are frequently associated with tibial shaft and plateau fractures, but superior dislocations can also occur with high-energy ankle injuries. 9,12,15 Herzog et al 16 reported an incidence of 1.5% and 1.9% of PTFJ dislocation in all tibial shaft and tibial plateau fractures, respectively. These results were supported by Haupt et al 17 who found an incidence of PTFJ dislocation in tibial shaft fractures of 1.06%.…”
Section: Patient Presentationmentioning
confidence: 99%